Terra Incognita: Results of Polish excavations in Albania and Montenegro - Dyczek, Piotr (Studia Europaea Gnesnensia, 2017)
One of the most important issues in Illyrian archeology today concerns the origins of Illyrian cities. The excavations at Rhizon have provided new data on the subject where many elements of the ancient urban architecture have been recorded. First, the monumental defense walls so called – Cyclopean wall. The lower town was divided into districts, but it was not an orthogonal plan. The architecture of the houses in generally Hellenistic in nature, but always a variation on the standard model in use each of the six insulae. Despite the limited size of the excavation compared to the overall size of the town, three separate bathrooms with terracotta baths have been unearthed, including a bathtub for children. In considering the urban structure of Rhizon the archaeologists had to come to grips with the question of the ruling authority and its architectural emanation. In terms of the functioning of royal authority in Illyria, the discovery of a palatial complex in Rhizon has added immensely to our knowledge. The older complex, included a megaron-type hall with a central hearth, storerooms and large courtyard The area was rebuilt after the event. The rubble was leveled, the storerooms reconstructed. The old megaron was turned into a kitchen and/or banquet hall attached to the new palace, which was built in part in the old courtyard. Part of the courtyard now served as a roadleading along the new palace facade. The younger palace was raised of neatly dressed ashlar blocks of limestone joined by the Greek technique of anathyrosis. Excavation in the other capital of Illyria, Scoder, open the way to interesting considerations in reference to the above. One of the most interesting discoveries was made during an investigation of a cistern constructed in Venetian times and rebuilt by the Turks. Two inscriptions, one whole and the other fragmentary, were immured into the central pillar supporting the roof of the cistern. Three inscriptions were preserved on one of these two blocks. On the one ofthe Latin text, Scoder is mentioned as a Roman colony. In late Roman times Scoder was the capital of the Praevalis province. The wall, excavated by us, surrounding the lower town dates to this period. One of the mysteries of Scoder was a bulwark below the north wall of the fortifications The present investigations have identified the wall as a defensive structure raised by the Venetians during the Turkish siege of 1478/1479. Three other interesting discoveries concern the 17th and 18th centuries. A set of almost 30 glass aryballoi were found in the ruins of one of the Turkish houses. Another hoard, found this time in a water sewer which is always interesting to the archaeologist, contained a small bag of silver coins struck in Dubrovnik in the early 17th century as well as a series of majolica vessels covered with a colored glaze and even some imported Chinese porcelain. An apothecary's shop in the lower town yielded the remains of scales, vessels and a well preserved small tin pyxis The inscription on its cover identifies its content as „thyriaca”, an antidote known to English apothecaries as Venice treacle.